Achieving academic control in two languages: Drawing on the psychology of language learning in considering the past, the present, and prospects for the future - Cohen, Andrew D. (Studies in Second Language Learning and Teaching, 2015)
This paper first considers what it means to become truly proficient in a language other than the native one. It then looks briefly at the evolution of dual language programs. Next, it focuses on the issue of whether the first language (L1) or the second language (L2) serves as the language of mediation. Other dual language program issues are then discussed, such as how proficient learners actually become in academic and social language in the L2, their proficiency in grammar and pronunciation, and possible administrative constraints in the design and execution of such programs. Finally, attention is given to a guidebook written directly for dual language learners and for their teachers in which learners are encouraged to take a proactive role to ensure that they make the most of their dual program language learning and use experiences.